The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1007/bf01907060
|View full text |Cite
|
Sign up to set email alerts
|

The role of lipid peroxidation in pathogenesis of arrhythmias and prevention of cardiac fibrillation with antioxidants

Abstract: The present paper shows the arrhythmogenic effect of a direct induction of lipid peroxidation (LP) on isolated auricles; it is demonstrated that preendured stress potentiates this effect, while antioxidants prevent it. Subsequently, in studying the mechanism of the LP arrhythmogenic effect it was established that stress, like the LP induction, disorders the activity of Na, K-ATPase and accelerates thermodenaturation of this enzyme which plays a key role in maintaining the transmembrane potential and the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
1
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 31 publications
0
11
1
1
Order By: Relevance
“…29) Oxygen-derived free radicals might play a key role in the genesis of ventricular arrhythmias. 30) However, we did not identify a significant correlation between oxidative stress and the development of reperfusion-induced arrhythmia.…”
Section: Discussioncontrasting
confidence: 62%
“…29) Oxygen-derived free radicals might play a key role in the genesis of ventricular arrhythmias. 30) However, we did not identify a significant correlation between oxidative stress and the development of reperfusion-induced arrhythmia.…”
Section: Discussioncontrasting
confidence: 62%
“…The most important causes of sudden death following spontaneous restoration of integrate flow remain VT and VF [33]. Oxygen-derived free radicals might play a key role in the genesis of ventricular arrhythmias [34]. ATG is an active lignin isolated from Arctium lappa and has anti-inflammation, immunemodulatory, anti -microbial, anti-viral, anti-proliferative, anti-platelet aggregation, anti -carcinogenic and vasodilatory properties [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, ventricular tachycardia and ventricular fibrillation remain the most important causes of sudden death following spontaneous restoration of antegrade flow [14,16]. It was suggested that oxygenderived free radicals might play a key role in the genesis of ventricular arrhythmias [17,18].…”
Section: Reperfusion Arrhytmiasmentioning
confidence: 99%